Estudo das propriedades estruturais dos catalisadores de Cu e Cu-Ce suportados em alumina aplicados à reação de deslocamento gás-água - Caldas, Paula Cristina de Paula (2013)
Particle size effect and Ce addition on the catalytic properties of Cu/Al2O3catalysts were investigated for the water gas shift reaction (WGS). The catalysts were prepared by dry impregnation of an aqueous solution of nitrates of the respective metals on alumina, synthesized by sol-gel method. Samples were prepared with 5, 10 and 15% w/w of metallic copper and 12% w/w of CeO2. The catalysts were characterized by X-ray diffraction (XRD), temperature programmed reduction (TPR) spectroscopy, X-ray absorption (XAS). The WGS reaction was performed with reagents ratio of H2O:CO = 1:3 with temperature range from 200 to 350° C. The crystallites CuO were not detected by XRD. As the Cu content increased, the crystallite size of CeO2 decreased with a fluorite type structure from 7.4 to 3.4 nm. The results of TPR showed that the interaction Cu-O-Al was crucial to reduce temperature and ceria addition on the catalysts did not affect the temperature reduction of the CuO. The XANES in situ results along the WGS reaction showed that metallic Cu predominated and ceria was partially reduced. EXAFS results showed that the Cu particle size increased from 0.65 to 0.91 nm with an increased load of copper from 5 to 15%, respectively. After the reduction, step prior to reaction, the catalysts were not completely reduced. The degree of reduction increased with the Cu particle size and it was also dependent on the temperature and the oxidation potential of mixing of the reactants. The addition of ceria did not change the degree of reduction of samples Cu/Al2O3. The results suggest that the Cu particles have a reduced Cu core covered with an oxide layer. The catalytic activity increased as the Cu particle size decreased, which can be associated with the presence of the redox couple Cu+/Cu0. This provides a possibility of CO oxidation and its reoxidation due to water activation. The ceria addition also increased catalytic activity and it is probably attributed to activation of the water on the surface of ceria, followed by transfer of oxygen from its structure to the oxidation of CO in an interface Cu-CeO2.